Pengaruh Jenis Biochar dan Takaran Pupuk Kandang Sapi terhadap Pertumbuhan dan Hasil Kacang Hijau (Vigna radiata L.) - Felix Nahak Berek; Eduardus Yosef Neonbeni (Savana Cendana, 2018)
The aim of the study was to obtain the type of biochar and doses of cow manure which had an effect on the growth and yield of mung beans. This study used a 3 x 3 factorial randomized block design that was repeated 3 times. The first factor is the type of biochar consisting of 3 levels, namely without biochar, rice husk biochar, sawdust biochar, which is given as much as 1.5%. The second factor is the dose of cow manure consisting of 3 levels, namely without cow manure, 1 t / ha cow manure, 3 t / ha cow manure. This research was carried out from May to November 2017 on farmers' land in Lorotolus Village, Wewiku Subdistrict, Malaka Regency, East Nusa Tenggara. The results showed no interaction between the treatment of biochar types and doses of cow manure on the growth and yield of green beans. Sawdust biochar increased seed weight per plant and seed weight per hectare, doses of cow manure 1 t / ha increased seed weight per hectare and cow manure increased soil moisture content, increased seeded seed weight per plant and seed weight per hectare.